A critical appraisal of realist international relations concepts in the Horn of Africa-Persian Gulf relations: The state, power, and agency - Ylönen, A. (Cadernos de Estudos Africanos, 2022)
International Relations literature (re)produces principally “realist” depictions of relations between the Horn of Africa and the Persian Gulf. It portrays states as monolithic actors and the Persian Gulf countries as superior according to a state-centric conception of power and fails to recognize the agency of various African state and non-state actors and understand power in their external relations. This article discusses caveats of the key concepts of the realist approach and argues that it provides an inadequate analytical frame when applied to the Horn of Africa-Persian Gulf relations. The article calls for a broader approach that enables a better understanding of multiple actors that engage in international relations, enabling a more accurate analysis that helps to improve both theory and practice.